Intracochlear Pressure Transients During Cochlear Implant Electrode Insertion. Issue 10 (December 2016) - Greene, Nathaniel T.; Mattingly, Jameson K.; Banakis Hartl, Renee M.; Tollin, Daniel J.; Cass, Stephen P.
Abstract : Hypothesis: Cochlear implant (CI) electrode insertion into the round window induces pressure transients in the cochlear fluid comparable to high-intensity sound transients. Background: Many patients receiving a CI have some remaining functional hearing at low frequencies; thus, devices and surgical techniques have been developed to use this residual hearing. To maintain functional acoustic hearing, it is important to retain function of any hair cells and auditory nerve fibers innervating the basilar membrane; however, in a subset of patients, residual low-frequency hearing is lost after CI insertion. Here, we test the hypothesis that transient intracochlear pressure spikes are generated during CI electrode insertion, which could cause damage and compromise residual hearing. Methods: Human cadaveric temporal bones were prepared with an extended facial recess. Pressures in the scala vestibuli and tympani were measured with fiber-optic pressure sensors inserted into the cochlea near the oval and round windows, whereas CI electrodes (five styles from two manufacturers) were inserted into the cochlea via a round window approach. Results: Pressures in the scala tympani tended to be larger in magnitude than pressures in the scala vestibuli, consistent with electrode insertion into the scala tympani. CI electrode insertion produced a range of pressure transients in the cochlea that could occur alone or as part of a train of spikes with equivalent peak sound pressure levels in excess of 170 dB sound pressure level. Instances of pressure transients varied with electrode styles. Conclusion: Results suggest electrode design, insertion mechanism, and surgical technique affect the magnitude and rate of intracochlear pressure transients during CI electrode insertion. Pressure transients showed intensities similar to those elicited by high-level sounds and thus could cause damage to the basilar membrane and/or hair cells.